THE IMPLEMENTATION OF SAVI (SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL) TO INCREASE THE STUDENTS’ ENGLISH STRUCTURE SKILL AT ENGLISH EDUCATION DEPARTMENT - Rijal, Samsi; Arifah, Nurdiana (Universitas Nusantara PGRI Kediri, 2020)
This research begun from the students’ problems in understanding the English structure at the first semester of English Education Department, Teacher Training and Education Faculty, Madura Islamic University (UIM) Pamekasan. From the data, it showed that most of students did not achieve the target score 75 (B), it was only 43.75% students. These problems occurred because 1) they used to memorize the pattern of English structure, 2) they seldom practice it in spoken or written, 3) they felt afraid of making mistakes. Concerning with these, the researcher tried to solve by implementing an appropriate strategy, it is SAVI (SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL) which was introduced by Dave Meire. The research design is Classroom Action Research (CAR). It was done in two cycles with four steps; planning, acting, observing and reflecting. After conducting the research, there were significant improvements of students’ score. From the data, in the preliminary study, there were only 43.75% who achieved the target score. After implementing SAVI in the cycle I, there were improvement of students score, it was 62.5% students who achieved the target score. In cycle II, there were 87.5% students. From the data above, it could be concluded that implementing SAVI is success because it achieved the target score, it is more than 85% students got 75 (B). Keyword : SAVI (SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL), English Structure.